ANALISIS HASIL VALIDASI AHLI PADA PENGEMBNAGAN VIDEO PEMBELAJARAN ENERGI TERBARUKAN BERBASIS CONTEXTUAL, TEACHING AND LEARNING (CTL) - Aureli, Bunga Zahaa; Amin, Ahmad; Lovisia, Endang (LP2M IAIN Sultan Amai Gorontalo, 2026)
This purpose of this study was to analyze the results of the validation of learning videos based on Contextual, Teaching and Learning (CTL). The type of research is Research and Development (R&D) with a development model of 4D (define, design, development and disseminate). The type of research method is by calculating the feasibility value in the form of a quantitative score then converted into qualitative data (interval) with a scale of five. The data analysis technique is carried out using product validation techniques. Validation is carried out with Material Experts, Media Experts and Language Experts. The feasibility of the Material obtained a score of 33 with an assessment range of 28 < X ≤ 34, including the feasible category. The media feasibility component obtained a score of 38 with a range of x > 34, including the Very feasible category. The language feasibility component obtained a score of 32 with an assessment range of 28 < X (<) 34, including the feasible category. The recapitulation of the total assessment score from the validator obtained a score of 103 with a range of x > 102, including the very feasible category. So it can be said that the Contextual, Teaching and Learning (CTL) based learning video developed is very feasible to be tested in the next stage.